Macroprudential policy with capital buffers - Josef Schroth (Bank of Canada, 2019)
This paper studies optimal bank capital requirements in a model of endogenous bank funding conditions. I find that requirements should be higher during good times such that a macroprudential "buffer" is provided. However, whether banks can use buffers to maintain lending during a financial crisis depends on the capital requirement during the subsequent recovery. The reason is that a high requirement during the recovery lowers bank shareholder value during the crisis and thus creates funding-market pressure to use buffers for deleveraging rather than for maintaining lending. Therefore, buffers are useful if banks are not required to rebuild them quickly.
Keywords: E13; E32; E44; 330; Credit and credit aggregates; Financial stability; Financial system regulation and policies; Business fluctuations and cycles; Credit risk management; Lender of last resort